The role of the curriculum in the reproduction of ethnic-racial inequalities. A look at the Argentine case from a Latin American perspective (Revista INTEREDU11, 2021)
This article describes how the school curriculum in Latin America has been consolidated from a Eurocentric vision that, through denial and submission and non-hegemonic cultures, has contributed to sustaining ethnic-racial inequalities, exclusion and epistemic racism present in our societies. It is an essay that states that the curriculum is not a neutral element. The Argentine case describes how the process of selection of content, knowledge, values and ideologies that condenses the curriculum, has reaffirmed the positions that exclude ethnic diversity and reinforce the idea of a supposed homogeneous society. At the same time, it shows that today the struggles for control of the curriculum are far from disappearing. They continue through different actors who seek to shape it according to their interests. Finally, the article raises the question about the challenges currently posed by the development of a plural and intercultural school curriculum, capable of dialoguing with the enormous problems facing Latin America and of providing tools for a rapidly evolving world.